1999
DOI: 10.1177/135245859900500412
|View full text |Cite
|
Sign up to set email alerts
|

Measuring evoked responses in multiple sclerosis

Abstract: Evoked potentials (EPs) have been widely utilised in Multiple Sclerosis (MS) patients to demonstrate the involvement of sensory and motor pathways. Their diagnostic value is based on the ability to reveal clinically silent lesions and to objectivate the central nervous system damage in patients who complain frequently of vague and indefinite disturbances which frequently occurs in the early phases of the disease. The advent of magnetic resonance imaging (MRI) techniques has greatly reduced the clinical utilisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 43 publications
2
20
0
2
Order By: Relevance
“…By comparison, prospectively acquired follow-up of EP findings and clinical course in other MS cohorts has ranged from 2-3 years. 11,[17][18][19][20] The present results are in agreement with the study of Leocani et al 18 and Jung et al 19 in which however the EP results were transformed to ordinally scaled data and also included qualitative assessments of potentials in spite of their high inter-rater variability 21 and the problem of downgrading numerical information to an ordinal level. 22 The latter procedure might be the reason for the absence of predictive power of EPs in the study of O'Connor et al 17 A comparison with the study by Kallmann et al 23 is more difficult, due to its retrospective design.…”
Section: Discussionsupporting
confidence: 86%
“…By comparison, prospectively acquired follow-up of EP findings and clinical course in other MS cohorts has ranged from 2-3 years. 11,[17][18][19][20] The present results are in agreement with the study of Leocani et al 18 and Jung et al 19 in which however the EP results were transformed to ordinally scaled data and also included qualitative assessments of potentials in spite of their high inter-rater variability 21 and the problem of downgrading numerical information to an ordinal level. 22 The latter procedure might be the reason for the absence of predictive power of EPs in the study of O'Connor et al 17 A comparison with the study by Kallmann et al 23 is more difficult, due to its retrospective design.…”
Section: Discussionsupporting
confidence: 86%
“…Conduction time, a demyelination marker, is the main electrophysiological characteristic described so far in many EP studies on patients with clinically definite MS, due to its high sensitivity and good reproducibility [18,21,29]. Though sometimes included in ordinal scores [11,19], amplitude has rarely been used as an individual score because of its higher variability even in normal subjects.…”
Section: Discussionmentioning
confidence: 98%
“…For monitoring the disease course, the use of only the most robust EP components has been recommended (Comi et al 1999) and has been found useful (Fuhr et al 2001; Schlaeger et al 2012a, b, 2013). In the present study, the P100 latency shows highest test–retest reliability in the same range as reported previously (Meienberg et al 1979; Thomae et al 2010) and is the main factor in predicting diagnostic group and history of ON.…”
Section: Discussionmentioning
confidence: 99%